2019
DOI: 10.7287/peerj.preprints.27587v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential bias in peer review of grant applications at the Swiss National Science Foundation

Abstract: Background: The Swiss National Science Foundation (SNSF) supports fundamental and use-inspired research in all academic disciplines. As part of the evaluation procedure, grant applications to the SNSF are reviewed by external reviewers. The legitimacy of funding decisions depends on its ability to base funding decisions solely on the scientific merit of grant applications. Aim: We examined whether the following factors influenced the scores given to grant applications submitted to the SNSF: (1) source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Some studies have also shown that male reviewers were prone to give, overall, higher evaluations than female reviewers (e.g. Broder, 1993;Jayasinghe et al, 2003;Severin et al, 2019), although this effect was found to be rather modest (Severin et al, 2019). Additionally, the common assumption that external reviewers may hold preferences for applicants with the same or a specific gender (Jayasinghe et al, 2003) has been examined in grant schemes for the Australian Research Council (Jayasinghe et al, 2001(Jayasinghe et al, , 2003Marsh et al, 2008Marsh et al, , 2011, the Austrian Science Fund (Mutz et al, 2012), the German Boehringer Ingelheim Fonds , and the Swiss National Science Foundation (Severin et al, 2019), and none have substantiated the effect.…”
Section: Individual and Systemic Biasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have also shown that male reviewers were prone to give, overall, higher evaluations than female reviewers (e.g. Broder, 1993;Jayasinghe et al, 2003;Severin et al, 2019), although this effect was found to be rather modest (Severin et al, 2019). Additionally, the common assumption that external reviewers may hold preferences for applicants with the same or a specific gender (Jayasinghe et al, 2003) has been examined in grant schemes for the Australian Research Council (Jayasinghe et al, 2001(Jayasinghe et al, , 2003Marsh et al, 2008Marsh et al, , 2011, the Austrian Science Fund (Mutz et al, 2012), the German Boehringer Ingelheim Fonds , and the Swiss National Science Foundation (Severin et al, 2019), and none have substantiated the effect.…”
Section: Individual and Systemic Biasesmentioning
confidence: 99%
“…In addition to the insufficient number of eligible senior researchers, women, compared to men, are generally less inclined to apply for grant funding or renewal (Beck & Halloin, 2017;Blake & La Valle, 2000;Boyle et al, 2015;Friesen, 1998;Grant et al, 1997;Jayasinghe et al, 2003;Marsh et al, 2008;Pohlhaus et al, 2011;Severin et al, 2019;Ward & Donnelly, 1998). On a practical level, institutional support may not be available for eligible women to relieve them of administrative or teaching duties to prepare for the grant writing process or to support them in receiving the necessary training needed for preparing applications (Easterly & Pemberton, 2008).…”
Section: Social Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Criticisms particularly focus on a lack of consistency between reviewers in their evaluations of research quality (e.g. Bornman, Mutz & Daniel, 2010;Pier et al, 2018;Smith, 2006), and on the potential scope for bias in reviews (Marsh, Jayasinghe and Bond 2008;Severin, Martins, Delavy, Jorstad, & Egger, 2019). This paper uses heretofore unpublished data from the largest social-science funder in the UK (the Economic and Social Research Council; ESRC) to investigate issues of consistency and bias in peer-reviews of funding proposals.…”
Section: Introductionmentioning
confidence: 99%